Fe2O3–TiO2 Nanocomposites for Enhanced Charge Separation and Photocatalytic Activity. Issue 47 (3rd October 2014) - Moniz, Savio J. A.; Shevlin, Stephen A.; An, Xiaoqiang; Guo, Zheng‐Xiao; Tang, Junwang
Abstract Photocatalysis provides a cost effective method for both renewable energy synthesis and environmental purification. Photocatalytic activity is dominated by the material design strategy and synthesis methods. Here, for the first time, we report very mild and effective photo‐deposition procedures for the synthesis of novel Fe2O3–TiO2 nanocomposites. Their photocatalytic activities have been found to be dramatically enhanced for both contaminant decomposition and photoelectrochemical water splitting. When used to decompose a model contaminant herbicide, 2, 4‐dichlorophenoxyacetic acid (2, 4‐D), monitored by both UV/Vis and total organic carbon (TOC) analysis, 10 % Fe–TiO2–H2O displayed a remarkable enhancement of more than 200 % in the kinetics of complete mineralisation in comparison to the commercial material P25 TiO2 photocatalyst. Furthermore, the photocurrent is nearly double that of P25. The mechanism for this improvement in activity was determined using density functional theory (DFT) and photoluminescence. These approaches ultimately reveal that the photoelectron transfer is from TiO2 to Fe2O3. This favours O2 reduction which is the rate‐determining step in photocatalytic environmental purification. This in situ charge separation also allows for facile migration of holes from the valence band of TiO2 to the surface for the expected oxidation reactions, leading to higher photocurrent and better photocatalytic activity.